Exploring the superfocusing performance of plasmonic lenses formed by coupled nanoslits. (1st October 2016) - Zhu, Yechuan; Yuan, Weizheng; Yu, Yiting; Wang, Ping; Sun, Hao
Abstract : A comprehensive investigation on the superfocusing performance of a plasmonic lens formed by coupled metallic nanoslits is carried out. Based on the geometrical optics and the wavefront reconstruction principle, the nanoslit array for a plasmonic lens is optimally designed to achieve the desired phase modulation by considering the influence of the coupling between adjacent aperiodic nanoslits on phase delay and the theory of periodic metallic nanoslits. The designed lens' focusing behaviour is verified by using the finite‐difference time‐domain method. Numerical results demonstrate that the superfocusing performance of a plasmonic lens has a close relationship with the lens size, focal length, working medium and incident wavelength. A larger lens size, a shorter focal length, a higher‐index working medium can contribute to producing a higher‐resolution superfocusing. Moreover, due to the material response, a shorter wavelength is not beneficial for an efficient focusing.